2018
DOI: 10.1186/s40657-018-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

A potential distribution map of wintering Swan Goose (Anser cygnoides) in the middle and lower Yangtze River floodplain, China

Abstract: Background: Reliable information on the distribution of target species and influencing environmental factors is essential for effective conservation management. However, ecologists have often derived data from costly field surveys. The Swan Goose (Anser cygnoides), a vulnerable Anatidae species, winters almost exclusively in China's Yangtze River floodplain, but wintering numbers have been steadily decreasing. To better safeguard this unique species, modern modeling approaches can be used to quantify and predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Overall, we identified that climate plays a major role in regulating species suitability in wetlands. In particular, isothermality, representing the evenness of temperature relative to annual oscillations, was identified as the most important factor, which is consistent with previous findings (An et al., 2018; Garris et al., 2015). Isothermality influences the water supply of wetlands via its substantial impacts on seasonal hydrologic cycling, especially for wetlands reliant on the runoff from spring melt as their primary water source.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, we identified that climate plays a major role in regulating species suitability in wetlands. In particular, isothermality, representing the evenness of temperature relative to annual oscillations, was identified as the most important factor, which is consistent with previous findings (An et al., 2018; Garris et al., 2015). Isothermality influences the water supply of wetlands via its substantial impacts on seasonal hydrologic cycling, especially for wetlands reliant on the runoff from spring melt as their primary water source.…”
Section: Discussionsupporting
confidence: 91%
“…This latter feature is important because the species considered here all differ in their diet and habitat use. For example, the Swan Goose forages for submerged tubers (An et al 2018(An et al , 2019, Bean Goose grazes the above ground parts of Carex, as well as consuming grain seeds and plant buds (Yang et al 2016), while the family Gruidae can prey on fish, crustaceans, invertebrates and other animals (BirdLife International 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Swan Geese (Anser cygnoides) is an endemic East Asian species listed by IUCN as Vulnerable, which now breeds mainly in Mongolia and adjacent areas of Russia and China and migrates to winter almost exclusively in China (Batbayar et al 2011;An et al 2018;Damba et al 2020). The species has shown long-term major contractions of breeding and wintering range as well as recent continued declines in abundance (Fox and Leafloor 2018;Damba et al 2020).…”
Section: Introductionmentioning
confidence: 99%